Implementasi Destinasi Wisata Kuliner Berdasarkan Fatwa DSN MUI Nomor 108/DAN-MUI/X/2016 di Kota Bandung - Ghina Syifa Agustina; N. Eva Fauziah; Popon Srisusilawati (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. One of the MUI fatwas regarding tourism is contained in the Fatwa of the National Sharia Council of the Indonesian Ulema Council No. 108/DSN- MUI/X/2016. According to an article from Trip-Advisor, Indonesia's largest tourist reference social networking site also recommends "Hummingbird Eatery and Space" as one of the halal tourist attractions. Considering the misconception that claims about "Halal Tourism" are in accordance with sharia, it is important to carry out more in-depth research and study the implementation of culinary tourism destinations based on MUI fatwa Number 108/DSN-MUI/X/2016 in tourist destinations in the city of Bandung. This research aims to analyze the management of culinary tourism destinations at Hummingbird Eatery and Space and the implementation of culinary tourism destinations based on DSN-MUI Fatwa Number 108/DSN-MUI/X/2016 at Hummingbird Eatery and Space. This research uses qualitative methods, with data collection techniques through interviews, documentation, literature study and observation. The results of research at the Hummingbird Eatery and Space Restaurant show that there is a significant discrepancy with the DSN MUI Fatwa Number 108/DSN-MUI/X/2016 regarding the halalness of the food and beverages served. In fact, this restaurant does not hold an MUI halal certificate and there is no explicit clarification regarding the halal status of food ingredients from the manager. Thus, the implementation of the provisions for culinary tourism destinations carried out by Hummingbirds Eatery and Space is deemed not to be in accordance with the MUI DSN Fatwa Number 108/DSN-MUI/X/2016. However, on the one hand, this restaurant has implemented this fatwa in terms of providing facilities for places of worship and a clean environment. Keywords: Halal Tourism, MUI Fatwa, Culinary Tourism. Abstrak. Salah satu fatwa MUI mengenai pariwisata tercantum dalam Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia No. 108/DSN- MUI/X/2016. Menurut artikel dari Trip-Advisor, situs jejaring sosial referensi wisata terbesar Indonesia juga menyarankan “Hummingbird Eatery and Space” sebagai salah satu tempat wisata halal. Mengingat adanya miskonsepsi klaim atas “Wisata Halal” yang sesuai syariah tersebut, penting untuk dilakukan penelitian yang lebih mendalam dan dikaji terkait implementasi destinasi wisata kuliner berdasarkan fatwa MUI Nomor 108/DSN-MUI/X/2016 dalam destinasi wisata di Kota Bandung. Penelitian ini bertujuan untuk menganalisis pengelolaan destinasi wisata kuliner di Hummingbird Eatery and Space dan implementasi destinasi wisata kuliner berdasarkan Fatwa DSN-MUI Nomor 108/DSN-MUI/X/2016 di Hummingbird Eatery and Space. Penelitan ini menggunakan metode kualitatif, dengan teknik pengumpulan data melalui wawancara, dokumenasi, studi pustaka, dan observasi. Hasil penelitian di Restoran Hummingbird Eatery and Space menunjukan bahwa terdapat ketidaksesuaian yang signifikan dengan Fatwa DSN MUI Nomor 108/DSN-MUI/X/2016 terkait dengan kehalalan bahan makanan dan minuman yang disajikan. Bahkan resto ini tidak memegang sertifikat halal MUI dan tidak ada klarifikasi eksplisit mengenai status kehalalan bahan makanan dari managernya. Dengan demikian, implementasi ketentuan destinasi wisata kuliner yang dilakukan oleh Hummingbirds Eatery and Space dianggap belum sesuai dengan Fatwa DSN MUI Nomor 108/DSN-MUI/X/2016. Namun di satu sisi restoran ini telah menerapkan fatwa ini dari sisi penyediaan fasilitas tempat ibadah dan lingkungan yang bersih. Kata Kunci: Pariwisata Halal, Fatwa MUI, Wisata Kuliner.